Improvement of Recovery Performance in the Solvent Extraction of Cu(Ii) Using [Bmim][Tf2n] and a ?-Diketone as Extractant and Its Stripping with Supercritical Carbon Dioxide - Romero-Figueroa, J; Torres-Mediano, A; Plaza, A (Elsevier B.V., 2017)
This study deals with the improvement of the recovery performance in the solvent extraction of Cu(II) using the ionic liquid [bmim][Tf2N] and the β-diketone 1,1,1-trifluoro-2,4-pentanedione (TFA) as extractant and its stripping with supercritical carbon dioxide. This work describes a modified procedure, which shows better L-L extraction percentages with a decreasing of the concentration of TFA, the contacting time and the volumetric O/A ratio respect to the previously reported tests. Thus, the extraction was implemented with a concentration of TFA in [bmim][Tf2N] equal to 60 mol m−3, a contacting time of 5 min and an O/A ratio equal to 1:7. The stripping of the metal complex from the organic phase was achieved in semi-continuous mode with scCO2. This configuration allowed obtaining a stripping percentage higher than the obtained with a previously tested procedure in batch mode with a consumption of CO2 4.3 times lower than the observed one in previous work. © 2017 Elsevier B.V.